2021
DOI: 10.21203/rs.3.rs-605986/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malignant Transformation Of Fibrous Dysplasia In Combination With Bone Cyst: A Case Report.

Abstract: Background: Fibrous dysplasia and Simple bone cyst are all common benign lesions. A case of osteosarcoma developing from fibrous dysplasia in combination with unicameral bone cyst will be discussed. The radiologic, histologic characteristics and clinical prognostic of the patient will be described. As far as we know, this is the first case report of malignant transformation secondary to fibrous dysplasia in combination with unicameral bone cyst, which is extremely rare and worthy of clinical attention or vigil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Nine patients underwent tumor resection and 7 died afterward, with the average survival period reaching 5.3 years. It has been reported that 15 a patient with a cyst with tibial FD was treated with an intracapsular scraping of the tibial lesion. After 2 years of treatment, FD malignantly changed to osteosarcoma and the patient was treated with surgery again.…”
Section: Discussionmentioning
confidence: 99%
“…Nine patients underwent tumor resection and 7 died afterward, with the average survival period reaching 5.3 years. It has been reported that 15 a patient with a cyst with tibial FD was treated with an intracapsular scraping of the tibial lesion. After 2 years of treatment, FD malignantly changed to osteosarcoma and the patient was treated with surgery again.…”
Section: Discussionmentioning
confidence: 99%